Sistem Informasi Company Profile Bengkel Tralis Mang BUUK Berbasis Web Menggunakan Skala Likert - Yanti Amaliasari; Yanti Amaliasari (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This study aims to measure user satisfaction with the Web-Based Company Profile Information System for Tralis Workshop, which was developed as a digital platform for information dissemination and business promotion. The measurement was conducted using the User Satisfaction method, which includes three main dimensions: system quality, information quality, and service quality. A quantitative descriptive approach was applied, and data were collected through a five-point Likert scale questionnaire distributed to 30 respondents, consisting of workshop owners, employees, and customers. The analysis results indicate that system quality achieved an average score of 4.35 or 87% (very satisfied category), information quality reached 4.21 or 84.2% (satisfied category), and service quality obtained 4.12 or 82.4% (satisfied category). Overall, the user satisfaction level reached an average score of 4.23 or 84.6%, categorized as satisfied. These findings demonstrate that the system successfully meets user expectations, particularly in terms of usability, access speed, and clarity of information. Furthermore, the implementation of this web-based information system effectively enhances the workshop’s professional image, strengthens its promotional reach, and serves as a model for user-oriented digital transformation among small and medium-sized enterprises (SMEs).